Lectura compartida y las macrodestrezas en la asignatura Lengua y Literatura del sexto grado “D”, escuela “Alonso de Mercadillo”, Loja 2021-2022. - Flores Quezada, Daniela Alejandra (2022)
The following research called reading and macro-skills has the general objective of contributing to the improvement of the strengthening of listening, speaking, reading and writing skills through shared reading in sixth grade students of the Basic Education School "Alonso de Mercadillo", to fulfill this objective, three specific objectives were developed, the first focused on identifying the purposes of shared reading that contribute to the strengthening of the macro-skills, the second on determining the characteristics of the macro-skills that favor oral and written communication, and the last objective was aimed at implementing a didactic proposal through shared reading for the strengthening of the macro-skills in the subject of Language and Literature. To carry out this study a descriptive type of research was used, with a quantitative-qualitative approach and non-experimental design, during the process the scientific, observational, descriptive, hermeneutic, inductive and statistical methods were applied, the techniques used were observation, survey, pre - evaluation and post - evaluation, in the same way the instruments used were the observation sheet, questionnaire, pre - evaluation and post - evaluation questionnaire, these contributed significantly in the data collection, the research population was the "Alonso de Mercadillo" school, from which 31 students and one teacher were selected through a non-probabilistic sampling. It is important to mention that the results of the research indicate that the main purposes of shared reading contribute in a significant way to enhance the different characteristics of the macro-skills of listening, speaking, reading and writing, as evidenced by the application of the didactic proposal where shared reading helped students develop skills conducive to oral and written communication. Key words: Shared reading, purposes of shared reading, macro skills, activities for macro skills